Muslim Societies in Postnormal Times Foresights for Trends, Emerging Issues and Scenarios - Sardar, Ziauddin (International Institute of Islamic Thought, 2019)
Where will Muslim societies be tomorrow? The world is increasingly and constantly changing, making it hard to keep up. This makes the state much more dire and troublesome for those already marginalised - particularly Muslim societies. Normal is no longer capable of upholding the promise of tomorrow's certainty. These are postnormal times. In this storm of ignorance and uncertainty, Muslim societies stand to lose the most. But this is not destiny. In the cultivation of a new type of literacy - futures literacy - there resides a hope. Muslim Societies in Postnormal Times offers an alternative where we can 'rescue' and decolonise our futures. Sardar, Serra, and Jordan take an open and plural approach to the future revealing the true potentials that lie before us. Through detailed analysis of contemporary trends, the road to destruction is revealed. Through identifying and exploring emerging issues, agency through options can allow for positive change. And in the extrapolation of these ideas into scenarios, the authors pave the way for us to navigate our own preferred futures. Their study challenges the reader to think about the future in a new way, redefining the monolithic future as three tomorrows (Extended Present, Familiar Futures, and Unthought Futures), along the way ever watchful for Black Swans, Black Elephants, and the illustrious Black Jellyfish that could disrupt the path ahead. The authors pull no punches in critically evaluating the possibilities and nightmares that could potentially befall Muslim societies. Through a display of creativity and imagination, this book looks beyond the conventional to illuminate impacts in the context of the complex, interconnected world we find ourselves in. This informative and enlightening text will push readers to see beyond popular, yet native notions of present and future. In the exposition of the reader's ignorance and uncertainty, they will begin to look for the unthought and take agency in recolonising and navigating their preferred tomorrow.